Clinical and economic outcomes among injection-naïve patients with type 2 diabetes initiating dulaglutide compared with basal insulin in a US real-world setting: the DISPEL Study. Issue 1 (9th December 2019) - Mody, Reema; Huang, Qing; Yu, Maria; Patel, Hiren; Zhang, Xian; Wang, Liya; Grabner, Michael
Abstract : Aims: To report 1-year clinical and economic outcomes from the retrospective DISPEL (Dulaglutide vs Basal InSulin in Injection Naïve Patients with Type 2 Diabetes: Effectiveness in ReaL World) Study. Materials and methods: This observational claims study included patients with type 2 diabetes (T2D) and ≥1 claim for dulaglutide or basal insulin between November 2014 and April 2017 (index date=earliest fill date). Propensity score matching was used to address treatment selection bias. Change from baseline in hemoglobin A1c (HbA1c) was compared between the matched cohorts using analysis of covariance; diabetes-related costs were analyzed using generalized linear models. Results: Matched cohorts (903 pairs total; 523 pairs with complete cost data) were balanced in baseline characteristics with mean HbA1c 8.6%, mean age 54 years. At 1 year postindex, dulaglutide patients had significantly greater reduction in HbA1c than basal insulin (−1.12% vs −0.51%, p<0.01), lower medical costs (3753 vs 7604, p<0.01), higher pharmacy costs (9809 vs 6175, p<0.01), and similar total costs (13 562 vs 13 779, p=0.76). Medical and total costs per 1% HbA1c reduction were lower for dulaglutide than basal insulin (medical: 3128 vs 12 673, p<0.01; total: 11 302 vs 22 965, p<0.01), while pharmacy costs per 1% HbA1c reduction were lower without reaching statistical significance (8174 vs 10 292, p=0.15). Conclusions: In this real-world study, patients with T2D initiating dulaglutide demonstrated greater HbA1c reduction compared with those initiating basal insulin. Although total diabetes-related costs were similar, the total diabetes-related costs per HbA1c reduction were lower for dulaglutide, highlighting the importance of evaluating effectiveness along with the economic impact of medications.